2016
DOI: 10.18404/ijemst.44833
|View full text |Cite
|
Sign up to set email alerts
|

STEM Images Revealing STEM Conceptions of Pre-Service Chemistry and Mathematics Teachers

Abstract: Article HistoryReceived: 2 August 2015 Science, technology, engineering, and mathematics (STEM) education has been an integral part of many countries' educational policies. In last decade, various practices have been implemented to make STEM areas valuable for 21st century generation. These actions require reconsideration of both pre-and in-service teacher education because those who touch students in and out of the class settings are the teachers. In this respect, this phenomenograhic study aimed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 12 publications
1
60
0
16
Order By: Relevance
“…It was determined that pre-service science teachers developed positive perspectives towards STEM. This result shows that STEM education has positive perspectives towards STEM, which has been confirmed by many studies (Akaygun & Aslan-Tutak, 2016;Adams, Miller, Saul & Pegg, 2014;Corlu, Capraro &Capraro, 2014;Yenilmez & Balbag, 2016;Yildirim & Selvi, 2015;). This also showed that pre-service science teachers had positive awareness of STEM.…”
Section: Discussionsupporting
confidence: 77%
“…It was determined that pre-service science teachers developed positive perspectives towards STEM. This result shows that STEM education has positive perspectives towards STEM, which has been confirmed by many studies (Akaygun & Aslan-Tutak, 2016;Adams, Miller, Saul & Pegg, 2014;Corlu, Capraro &Capraro, 2014;Yenilmez & Balbag, 2016;Yildirim & Selvi, 2015;). This also showed that pre-service science teachers had positive awareness of STEM.…”
Section: Discussionsupporting
confidence: 77%
“…However, the technological knowledge referred to in TPACK studies is generally the knowledge related to digital technologies. For this reason, technological knowledge is mostly seen as the knowledge of computers, the internet/web and digital materials (Akaygun & Aslan-Tutak, 2016;Archambault & Crippen, 2009). When this perspective is widened, technological knowledge is stated as knowing and using computer software (operating system, basic office programs, and software peculiar to the area of instruction, etc.…”
Section: Technological Knowledgementioning
confidence: 99%
“…As the field of education changes globally, traditional STEM education is becoming transdisciplinary . Hence, the arts (STEA(arts)M) are being included with the sciences, technology, engineering, and mathematics.…”
Section: Steam and Nursing Educationmentioning
confidence: 99%